Двор на Поварской - Рождественская Екатерина Робертовна (Девочка с Патриарших, 2022)
Экземпляры: ЦБ (20230511) / Инвентарный номер: 57783 / Цена: 427.25 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Р 62 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-4